Initial Properties Identification of Refined- and Semi Refined-Carrageenans as Raw Materials for Biodegradable Plastic Production - Bakti Berlyanto Sedayu; Putri Wullandari; Arif Rahman Hakim; Dina Fransiska (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2021)
Powdered refined- and semi-refined carrageenans (RC and SRC) have been characterized as alternative raw materials for industrial bioplastic production. Several basic parameters, i.e., the melting temperature, crystallinity, chemical structure (FTIR), and tensile properties, were observed. The melting temperature of RC was slightly higher than that of SRC, i.e., 176 °C and 172 °C, respectively. These temperatures were corresponded to their crystallinity degree (performed by X-ray diffraction). Nonetheless, the SRC demonstrated an overall higher thermal stability during heating. RC produced a clear transparent film. Meanwhile, SRC was yellowish and less transparent. The overall mechanical properties showed that RC produced more flexible film than SRC. However, both materials showed relatively equal tensile strength. In general, RC and SRC could be potentially used for biodegradable film production with different applications. RC was suitable for a flexible and clear plastic film, whereas SRC was suitable for rigid plastic film applications.